Analisis Faktor – Faktor Keuangan yang Mempengaruhi Peringkat Obligasi (Studi Kasus Pada Perusahaan Manufacture yang Terdaftar Di Bursa Efek Indonesia) Periode 2016 – 2020 - Sahara, Retno Wardatus (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the effect of productivity, profitability, growth and leverage on bond ratings (Case Study of Manufacturing Companies Listed on the Indonesia Stock Exchange). The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange with a total sample of 17 companies. The sampling method used is purposive sampling method. The data source used is secondary data and technical data analysis using logistic regression analysis. The results of this study indicate that productivity, profitability, growth and leverage simultaneously affect the bond ratings of manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. Partially productivity, profitability, growth and leverage affect the bond ratings of manufacturing companies listed on the Stock Exchange Indonesia period 2016 – 2020. Keyword: Bond Rating, Productivity, Profitability, Growth and Leverage